A Community-Driven Usability Evaluation: The Case of the Inuvialuit Settlement Region Digital Library - Stobbs, Robyn; Shiri, Ali; Farnel, Sharon; Cockney, Cathy; Rathi, Dinesh; Campbell, Sandy (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2018)
This paper reports a usability evaluation study of the Digital Library North prototype that was conducted in May 2016. It proposes a culturally-aware and community-informed approach to the usability of digital libraries for Northern communities in Canada along with the emerging themes and the changes that were implemented as a result of the evaluation.